Comparison of Staining Techniques for Age Determination of Some Chondrichthyan Species - Basusta, Nuri; Demirhan, Sefa Ayhan; Cicek, Erdogan; Basusta, Asiye (Central Fisheries Research Inst, 2017)
In this study, six chondrichthyan species (Raja clavata, Raja miraletus, Raja asterias, Torpedo marmorata, Rhinobatos rhinobatos and Gymnura altavela) were captured for age determination in Iskenderun Bay (North eastern Mediterranean Sea) between May 2010 and January 2012. Age was determined from vertebral sectioned, using four staining techniques, namely Crystal Violet, Silver Nitrate, Safranin O and Alcian Blue. The results from these four techniques were compared to each other, with respect to visibility success on growth rings. Of all four staining techniques, Silver Nitrate staining provided the best optical resolution for growth rings of R. clavata, R. miraletus and R. rhinobatos. For, R. asterias, T. marmorata and G. altavela, however, it provided a lower optical resolution. In fact, four staining technique was also efficient for R. clavata. The most efficient staining techniques were Safranin O in T. marmorata and Alcian Blue in R. rhinobatos. The order of average readability scores for staining techniques was as follows: Silver Nitrate = Safranin O > Crystal Violet = Alcian Blue. A standardized staining methodology that can be used for all species studied, however, has not been achieved.
Bazı kıkırdaklı balık türlerinde yaş tayininde kullanılan boyama yöntemlerinin karşılaştırılması
Keywords: Age determination; Cartilaginous Fish; Crystal Violet; Silver Nitrate; Alcian Blue; Safranin O